High cadmium exposure impairs adult hippocampal neurogenesis via disruption of store-operated calcium entry - Guoqing Li; Caiyun Sun; Le Zhu; Yan Zeng; Jinquan Li; Yufei Mei (Ecotoxicology and Environmental Safety, 2024)
Cadmium (Cd) is a neurotoxicant that gradually accumulates in the human body with age. High Cd burden is correlated with adult hippocampal neurogenesis (AHN) and memory deficits in mammals. However, little knowledge is known about the mechanism by which Cd exposure impairs neurogenesis and cognition. Here, we investigated the roles of store-operated calcium entry (SOCE)-mediated calcium dyshomeostasis in Cd-induced AHN and memory deficits as well as therapeutic potential for the prevention of Cd-induced neurotoxicity. To achieve this goal, 8 weeks-old C57BL/6 J mice were subjected to different concentrations of cadmium chloride (0, 5, 10, 20 ppm) in drinking water for 8 weeks, we then examined the AHN, calcium homeostasis, SOCE channel and memory in Cd-exposed mice by using immunohistochemistry, calcium imaging, Y-maze and fear conditioning test. Our results indicated that chronic Cd exposure markedly increased Cd levels in serum and cerebrospinal fluid by almost 10-fold, and inhibited the proliferation and differentiation of hippocampal adult neural stem cells in a dose-dependent manner. Additionally, Cd exposure impaired the maturation of hippocampal neural stem cells without inducing gliosis. Transcriptome analysis revealed that Cd exposure inhibited the proliferation of neuroblastoma via alteration of calcium signaling pathway, and attenuated SOCE channels played a pivotal role in mediating Cd-induced cytoplasmic calcium overload and depletion of endoplasmic reticulum calcium stores. Activation of SOCE by hyperforin, a natural derivative from medicinal plant, restored intracellular calcium homeostasis and improved AHN and memory in Cd-exposed mice. Together, this study provided novel insights into the mechanism that Cd exposure impaired AHN and memory by prompting neuronal SOCE-mediated calcium dyshomeostasis, and offered a new therapeutic approach for prevention of Cd-induced neurotoxicity.